Corporate tax avoidance - the range of the problem and its effects on economy - Agata Iwasiuk (Institute of Economic Research (IER), 2016)
The main aim of this study is to draw attention to the significant problem of tax avoidance by multinational corporations. In the times of globalization, tax competition among countries and development of modern technology transnational corporations can operate with complex financial transactions to reduce to the minimum the amount of tax or completely avoid taxation. Governments in many countries due to the dreinage of public finances are forced to take measures that will minimize the range of the problem. Losses are counted in billons and there's a growing tendency. Without taxes, which are the basis for state's budget and finance all public good and services, further development of country is impossible. It is necessary for all countries to cooperate in order to counteract tax avoidance and develope new systems of taxation of multinational corporations.
Keywords: F5; F6; G3; H2; H3; 330; corporate tax avoidance; taxation; multinational corporations; globalization; tax havens; fiscal drainage